Foreign direct investment and trade - Kofi Aaron A-O Agyei-Henaku; Charlotte Badu-Prah; Akua Agyeiwaa-Afrane; Ferguson K. Gidiglo; Francis Yao Srofenyoh; Justice Gameli Djokoto (Economics and Econometrics Research Institute (EERI), 2024)
Eastern Europe experienced a surge in trade and capital movements after the introduction of the market economy. We investigate the substitution and complementary effect of foreign direct investment (FDI) and trade in the agricultural sector in Eastern Europe. We employed panel data from 1995 to 2020 for the 23 countries and fitted these to fixed and random effects estimators. We found that inward FDI did not influence trade. Outward FDI substituted exports and trade openness in the transition countries of Eastern Europe. However, outward FDI complemented imports and trade openness in Eastern Europe.
Keywords: F12; F14; 330; Complement; Eastern Europe; foreign direct investment; substitute; transition economies